The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s12884-021-04270-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and duration of prescribed opioid use during pregnancy: a cohort study from the Quebec Pregnancy Cohort

Abstract: Background Recent studies show a rapid growth among pregnant women using high potency opioids for common pain management during their pregnancy. No study has examined the duration of treatment among strong opioid users and weak opioid users during pregnancy. We aimed to investigate the prevalence of prescribed opioid use during pregnancy, in Quebec; and to compare the duration of opioid treatment between strong opioid users and weak opioid users. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 53 publications
(83 reference statements)
0
7
0
Order By: Relevance
“…The prevalence of opioid use during pregnancy is relatively similar across trimesters, suggesting that the timing and duration of exposure may have differential effects on the offspring ( Zhao et al, 2021 ). One caveat of studying prenatal opioid exposure in rodents is that the third trimester in humans corresponds to the first two weeks of postnatal life in rats ( Zeiss, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of opioid use during pregnancy is relatively similar across trimesters, suggesting that the timing and duration of exposure may have differential effects on the offspring ( Zhao et al, 2021 ). One caveat of studying prenatal opioid exposure in rodents is that the third trimester in humans corresponds to the first two weeks of postnatal life in rats ( Zeiss, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The review involved a meticulous examination of articles accessible through PubMed, published between January 2009 and December 2021, and conducted using the following keywords: 'pregnant,' 'addicted,' 'opioids,' 'NAS,' and 'withdrawal syndrome in obstetrics.' 1,2,4 The search encompassed relevant research from international sources as well as the Polish literature, considering articles available in Polish and English. 1,3 To ensure the inclusion of highquality research, particular attention was paid to the impact factor of the journals in which the articles were published.…”
Section: Methodsmentioning
confidence: 99%
“…Among pregnancies ending in delivery (249,234), 5.4% were exposed to opioids; the incidence of this phenomenon increased by 40.3% from 3.9% in 1998 to 5.5% in 2015, a significant increase was recorded in the 2nd and 3rd trimester of pregnancy. 4 A disturbing phenomenon was the rapid increase in the percentage of newborns with withdrawal syndrome. 2,3,5 As many as 2 out of 3 infants born with NAS were at risk of these complications because the mother used strong opioids during pregnancy.…”
Section: Addiction and Drug Abuse Trendsmentioning
confidence: 99%
“…The Pregnancy Risk Assessment Monitoring System (PRAMS) estimated that 6.6% of pregnant women reported using prescription opioids [ 8 ]. The Quebec Pregnancy Cohort study from 1998 to 2015 showed that 4.7% of pregnant women were exposed to opioids [ 9 ]. Limited data are available on the prevalence of substance use among pregnant women in Iran.…”
Section: Introductionmentioning
confidence: 99%